2020
DOI: 10.1039/d0py01006e
|View full text |Cite
|
Sign up to set email alerts
|

Command-destruct thermosets via photoinduced thiol-catalyzed β-scission of acyclic benzylidene acetals

Abstract: Photoinduced thiol-catalyzed hydrogen abstraction and ß-scission of acyclic benzylidene acetals is demostrated as a new route to “command-destruct” polymer thermosets. Using this approach, we show that poly(thioether acetal) networks synthesized...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…b) Efficient cleavage of the thermoset via the co‐monomer approach (cleavage of ten bonds in the case of both cleavable knots or cleavage linkage in the polymer backbone) adapted from ref. [19]. c) Resin formulation, preparation of 3D objects via VAT 3D printing, and cleavage mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…b) Efficient cleavage of the thermoset via the co‐monomer approach (cleavage of ten bonds in the case of both cleavable knots or cleavage linkage in the polymer backbone) adapted from ref. [19]. c) Resin formulation, preparation of 3D objects via VAT 3D printing, and cleavage mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of biomaterials, poly(propylene fumarate) (PPF) was also used to print stents, for example. [13] To increase the degradability, Bowman and Anseth [14][15][16][17] as well as Patton and coworkers [18,19] showed that the use of similar specific thiol-ene monomers containing a degradable core could be used. In this case, the use of thiol-ene chemistry allowed the preparation of more homogeneous networks that impart good degradation profile.…”
Section: Introductionmentioning
confidence: 99%
“…Photoprocessable moieties that react only under high irradiation intensities, long irradiation times, and non-overlapping excitation wavelengths have been designed for being compatible with photopolymerization. [29][30][31][32][33][34][35][36] However, methods for designing such materials limit the available wavelengths for photoprocessing and exclude photoreactive moieties that react rapidly under weak light irradiation. Directly over- coming this problem would advance the design and utility of photocontrollable materials, including the photo-molding of photodegradable materials and the fabrication of photoadhesives that are detachable via photodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, the photoprocessable moieties should remain intact during photopolymerization. Photoprocessable moieties that react only under high irradiation intensities, long irradiation times, and non‐overlapping excitation wavelengths have been designed for being compatible with photopolymerization [29–36] . However, methods for designing such materials limit the available wavelengths for photoprocessing and exclude photoreactive moieties that react rapidly under weak light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Separation of the polymerization and degradation processes has been established by a number of means, including using different wavelengths to activate radical-mediated polymerization of one group followed by direct photoscission of another, [29,30] using different wavelengths to activate separate polymerization and scission stages within the same functional group, [24] or using competing reactions with vastly different kinetics. [31] These general polymerizationthen-degradation processes have been used to create 3D prints with sacrificial scaffolds, [32] microelectronics arrays with Scheme 1. On-demand polymerizing-then-degrading networks were created by combining the thiol-ene polymerization reaction with radical-mediated thioaminal scission.…”
Section: Introductionmentioning
confidence: 99%